Ingrid Andree liest aus dem Tagebuch der Anne Frank;
Seite 1:<NZ>Ingrid Andree liest aus dem Tagebuch der Anne Frank, 1. Teil.<NZ><NZ>Seite 2:<NZ>Ingrid Andree liest aus dem Tagebuch der Anne Frank, 2. Teil.;